Evaluating Underlying Endocrine Abnormalities in Adolescents with Menstrual Disorders Presenting at a Tertiary Care Hospital - Maria Ali, Tahira Yasmeen, Zehra Naqvi, Rabia Farooqi, Saadia Khan, Bakhtawar, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Adolescence is a significant period between childhood and adulthood when physical and psychological changes occur along with menstruation. The onset of puberty is governed by genetic, endocrinal, neuronal, socioeconomic, and environmental factors. Endocrine abnormalities in adolescents are not uncommon and can lead to menstrual disorders. This study's objective is to identify the prevalence of underlying endocrine abnormalities and their association with menstrual disorders among adolescents at a tertiary care hospital in Pakistan. Material and Methods: We conducted a cross-sectional study of adolescent girls presenting with menstrual disorders at the Department of Obstetrics and Gynecology at Liaquat National Hospital, Karachi, Pakistan, from January 1, 2020, to January 1, 2021. We collected a detailed history from each patient. All physical examinations were performed in the presence of a female nurse, and we carefully maintained patient privacy. The physical examinations consisted of recording the patient's height, weight, body mass index (BMI), and thyroid examination. We also noted the patient's hirsutism score and the presence or absence of secondary sexual characteristics. All the patients received a hormonal evaluation in which we measured their thyroid-stimulating hormone levels, and follicle-stimulating hormone (on day two of their menstrual cycle and random FSH was measured for amenorrhea patients), prolactin, and free androgen index. Results: The study included 143 adolescent girls aged 10 to 19 with menstrual disorders such as primary amenorrhea, secondary amenorrhea, frequent menstrual bleeding, infrequent menstrual bleeding, shortened menstrual bleeding, heavy menstrual bleeding, and intermenstrual bleeding. The mean menarcheal age of the patient population was 12.1 ± 0.4 years, and the mean BMI was 25.27 ± 5.02 kg/m2. One hundred twenty-four patients (86.7%) reported polycystic ovarian syndrome (PCOS). Most PCOS patients had infrequent menstrual bleeding (85.5%), 46% had biochemical signs of hyperandrogenism, and 18.5% of PCOS patients showed clinical signs of hyperandrogenism. The most common menstrual problems reported by the patients were infrequent menstrual bleeding (74.1%), followed by shortened menstrual bleeding (61.5%), and heavy menstrual bleeding (9.8%). Thyroid dysfunction was present in the form of hypothyroidism (67.4%) and hyperthyroidism (32.6%). Over half of the hypothyroid patients (58.1%) presented with infrequent menstrual bleeding,41.9% presented with shortened menstrual bleeding and 41.9% with heavy menstrual bleeding .Infrequent menstrual bleeding (73.3%) and shortened menstrual bleeding (66.7%) were the most common menstrual problems in hyperthyroid patients. We found a significant association between thyroid disorder and infrequent menstrual bleeding (p=0.037), heavy menstrual bleeding (p<.001), and shortened menstrual bleeding (p=0.051). Heavy menstrual bleeding was also significantly related to hyperprolactinemia (p=0.036). Conclusions: Our study showed that endocrine abnormalities in thyroid dysfunction, PCOS, hyperprolactinemia, and hyperandrogenism could cause various menstrual problems in adolescent girls. Hence, underlying endocrine abnormalities need to be investigated and treated to improve adolescents' physical and mental well-being.